Floristic similarity between adult and saplings strata of Caatinga hyperxerophilous woody vegetation - a Brazilian seasonally tropical dry forest - Lucena, Marcelo Silva de [UNESP]; Holanda, Alan Caue de; Alves, Allyson Rocha (Inst Tecnologico Costa Rica, 2020)
In the Caatinga, the maintenance of forest ecosystems depends on natural regeneration and several factors that can act in two ways: 1) provide the perpetuation of communities composed of few species that dominate the adult and saplings strata, resulting in floristic similarities; 2) provide local differentiation between adult and saplings strata. However, these relationships remain poorly understood, as it is not known whether the factors acting on a local scale favor the floristic similarity between the adult and saplings strata or if these patterns are found in conserved and anthropized areas. This work evaluated the floristic similarity between the adult and saplings strata of hyperxerophilous caatinga woody-shrubby vegetation in conserved and anthropized areas. In two areas of conserved and anthropized hyperxerophilous Caatinga, adult and saplings individuals were measured and floristic richness and qualitative floristic similarity were evaluated. The floristic similarity between the adult and saplings strata was statistically compared using the Chao-Sorensen index. In both sites, although there was a large number of species exclusive to the adult stratum, the Chao-Sorensen index indicates high floristic similarity between strata. The analysis of this behavior together with the assessment of community structure shows that few species can be responsible for the key processes that structure and control the main mechanisms of persistence of these ecosystems. This can be attributed to the existence of locally uniform conditions that can define the dominance of adapted species groups.
Keywords: Semiarid vegetation; species richness and diversity; floristic composition; forest dynamics